Performing truth : works of radical memory for times of social amnesia - Bogad, L. M. (Routledge, Taylor & Francis Group, 2022)
"Performing Truth answers the most pressing questions facing any theatre makers who are wrestling with how to present historical, political or socioeconomic information in an engaging, entertaining and galvanising way. How to make data compelling and documents mobilizing? How to keep an audience interested in what might be dry, dire or depressing? How to surprise an audience and keep them alert? Collecting together the performance texts of international performance artist and activist L.M. Bogad, this book accompanies each script with essays that further explore that work's performance strategies. It also equips readers with specific resources and pedagogical tools to help those wishing to stage these pieces or create their own work to engage with similar topics. Bogad also provides 'takeaways' for each piece, illustrating the challenges of its particular subject matter and how to overcome those challenges with innovations unique to performance art. This is a key guidebook for artists and theatremakers facing the challenges of engaging with information in an era of fake news, propaganda bots, and the polarization of ideological spheres, as well as students and teachers taking on that challenge in theatre studies, performance studies and performing arts classrooms"--